Introducing Databases in Context Through Customizable Visualizations - Dietrich, Suzanne W.; Goelman, Don; Broatch, Jennifer; Crook, Sharon; Ball, Becky; Kobojek, Kimberly; Ortiz, Jennifer (Frontiers in Education, 2021)
The goal of the Databases for Many Majors project is to engage a broad audience in understanding fundamental database concepts using visualizations with color and visual cues to present these topics to students across many disciplines. There are three visualizations: introducing relational databases, querying, and design. A unique feature of these learning tools is the ability for instructors in diverse disciplines to customize the content of the visualization’s example data, supporting text, and formative assessment questions to promote relevance to their students. This paper presents a study on the impact of the customized introduction to relational databases visualization on both conceptual learning and attitudes towards databases. The assessment was performed in three different courses across two universities. The evaluation shows that learning outcomes are met with any visualization, which appears to be counter to expectations. However, students using a visualization customized to the course context had more positive attitudes and beliefs towards the usefulness of databases than the control group.